Proceedings of the Ninth Annual International Conference on International Computing Education Research 2012
DOI: 10.1145/2361276.2361280
|View full text |Cite
|
Sign up to set email alerts
|

A case study of environmental factors influencing teaching assistant job satisfaction

Abstract: Teaching assistants (TAs) play an integral role in teaching computer science undergraduates in North America. We report lessons in lab TA management, based on a case study which identified environmental factors affecting TAs' job satisfaction. These factors were identified through a series of semi-structured interviews about 23 lab sections taught at the University of British Columbia. We corroborated this with observational sampling of eight different TAs. Identified physical factors affecting job satisfactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Subsequently, recent studies have examined the behaviors of TAs, reporting for example on who initiates TA-student interactions [12] and the variations in the types, frequencies, and lengths of TA-student interactions that occur [13][14][15]. Despite this focus on the actions of TAs and instructors, the literature has not yet made connections between these behaviors and the student learning process and outcomes.…”
Section: B Literature Review and Motivationmentioning
confidence: 99%
“…Subsequently, recent studies have examined the behaviors of TAs, reporting for example on who initiates TA-student interactions [12] and the variations in the types, frequencies, and lengths of TA-student interactions that occur [13][14][15]. Despite this focus on the actions of TAs and instructors, the literature has not yet made connections between these behaviors and the student learning process and outcomes.…”
Section: B Literature Review and Motivationmentioning
confidence: 99%
“…We then added these questions: We performed 8 hours of observational study of TAs in their labs, observing how pairs worked together (described in [20]). After these observations, we went back to the interview scripts, and re-coded participants' answers about how they work with their partners and their experiences with their partners.…”
Section: Additional Analysismentioning
confidence: 99%
“…From a reliability point of view, it is an issue if the TAs construct their own criteria, especially since the interview results show our TAs work independently, as was also found in [29,30]. It has previously been shown that the reliability of the assessments was higher when the TAs carried out the assessment together [15] and that social aspects, such as collaborating with other TAs, affect job satisfaction [24]. Our TAs did state that they asked for help if they were unsure about an assessment (S5), but to also facilitate discussion before the assessments, could address any ambiguous phrasing in the instructions or criteria given, as also suggested regarding the use of grading rubrics in [27].…”
Section: Rq2 -What Materials and Instructions Are Needed?mentioning
confidence: 79%
“…TAs' development has also been studied, and formal mentorships have been suggested as training [25]. Social aspects have also been found to impact the job satisfaction of TAs in a computer lab setting [24]. To recruit students with sufficient knowledge and competency to be TAs is, of course, desirable and a suggestion on a rubric to do so has been presented in [18].…”
Section: Related Research and Theorymentioning
confidence: 99%
See 1 more Smart Citation